Comparative study of H-atom location, electronic and chemical bonding in ideal and vacancy containing-FCC iron - Rey Saravia, D. (2009)
We studied one of the aspects of iron embrittlement in an FCC lattice with a vacancy in the presence of hydrogen as an impurity. The energy calculations were performed using the ASED method (Atom Superposition and Electron Delocalization). The electronic structures were analyzed by the YAeHMOP program (extended Hückel Molecular Orbital Package). H in bulk FCC iron prefers octahedral sites while in the presence of a vacancy it is located near the defect in a position shifted from the center of the hole. The formed Fe-H bond makes the Fe-Fe bonds first neighbors to the vacancy 28% weaker with respect to the H-free structure.